Microencapsulation protects the biological activity of sea buckthorn seed oil - Zhang, Huirong; Song, Guanjie; Ma, Wenrui; Guo, Miaomiao; Ling, Xiao; Yu, Dan; Zhou, Weiqiang; Li, Li (Frontiers in Nutrition, 2023)
Introduction Sea buckthorn (Hippophae rhamnoides) seed oil is rich in unsaturated fatty acids, and is thus susceptible to oxidation and rancidity. Microencapsulation technology allows the effective protection of active substances, thereby prolonging the deterioration time and shelf life. Methods In this study, H. rhamnoides microcapsules were prepared using a spray-drying method, and the microencapsulation parameters were optimized. The morphological characteristics, structural parameters, and stability of the microcapsules were determined using scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, and oil oxidation stability testing. Results Based on encapsulation efficiency (EE, %) and the particle size (D50) of the microcapsules, the optimal preparation conditions were characterized as a wall material consisting of soy protein isolate and soybean polysaccharide (2:3), a wall concentration of 15%, a core-to-wall ratio of 1:3, and an inlet temperature of 160°C. Under these optimal conditions, the encapsulation efficiency was 95.30 ± 2.67%, with a yield of 57.03 ± 3.71% and a particle size of 7.96 ± 1.04 μm. Discussion Furthermore, the effectiveness of microencapsulation in protecting the biological activity of H. rhamnoides seed oil was confirmed by an antioxidation test. Thus, the results of this study showcase the successful microencapsulation of H. rhamnoides seed oil, thereby significantly improving its stability.